THE DEVELOPMENT OF TOURISM BASED ON LOCAL ECONOMIC IN PUJON KIDUL VILLAGE - NUTTAPOL - LERTSIRISAKULCHAI; Kaewketsaya Songthan; Pannipa Muangmontre; Atika Dwi Febriyanti; Ach. Apriyanto Romadhon (University of Muhammadiyah Malang, 2020)
The development of Tourism based on local economic is very important, and in many regions with unique physical characteristics that are rich in natural resources which can be further developed to be a popular tourist destination and able to stimulate the local economy such as together The purpose of this research is to find the development of tourism based on local economic in Pujon Kidul village and to find any problems and obstacles in local economic development of local government including the well-being of the community. The main problem that may be a deterrent to development is human resources from the community, because most people in the community There is still relatively little participation in community activities, including the interest in development. The research method used in this study is a qualitative research method, including secondary data and data collection from interviews. There is a descriptive description. Tourism development is based on the local economy, with an emphasis on management in two principles, agriculture and animal husbandry, from the results of this study it can be concluded that an important step in the development of local economy-based tourism is territorial diagnosis and institutional mapping, the process of growing sensitivity, and creating a local forum / regionally. The implementation of these three steps can be said to have been successfully implemented in Pujon Kidul village.Therefore, the study concludes that local economic development and the identification of obstacles to self-government, including what can be resolved quickly, make tourism development more efficient and lead to the fact that local people Can make money To the community for a better quality of life and well-being.